Implementation of thirst management in the immediate postoperative period guided by knowledge translation and exchange - Isadora Pierotti Carvalho; Aline Korki Arrabal Garcia; Marília Ferrari Conchon; Leonel Alves do Nascimento; Robertha Pickina Santos; Lígia Fahl Fonseca (Revista Gaúcha de Enfermagem)
ABSTRACT Objective: To evaluate the implementation of the Thirst Management Model in the immediate postoperative period guided by the Knowledge Translation framework. Method: A quasi-experimental study, in the Post Anesthesia Care Unit of a large university hospital in northern Paraná. Implementation took place in two phases: preparation and implementation and change. Data was collected by observing the practice of nursing professionals. The implementation process was evaluated by measuring adoption and aspects of fidelity, using descriptive analysis of the level of adherence to the evidence in the continuous improvement cycles and the reach of the target audience. The adoption of the Thirst Management Model at pre- and post-implementation times was compared using Chi-square. Results: In the pre-implementation period, 236 events in the care provided by nursing professionals related to thirst management were observed, and 198 in the post-implementation period. Adoption of the evidence went from 28.2% pre-implementation to 78.4% post-implementation (p<0.001). The level of adherence exceeded the 70% target in one of the three cycles: 61.1%, 66.6%, 84.0%. The target audience was reached 100% in the first rapid cycle. Conclusion: The use of the theoretical framework and its multifaceted intervention significantly increased the adoption of the Thirst Management Model.